How we are assessing the developing antibacterial resin-based dental materials? A scoping review. (August 2020) - Ibrahim, Maria Salem; Garcia, Isadora Martini; Kensara, Anmar; Balhaddad, Abdulrahman A.; Collares, Fabrício Mezzomo; Williams, Mary Ann; Ibrahim, Ahmed S.; Lin, Nancy J.; Weir, Michael D.; Xu, Hockin H.K.; Melo, Mary Anne S.
Abstract: Objectives: To identify antibacterial additives and screening/assessment approaches used to evaluate the antibacterial activity of resin-based restorative dental materials containing these additives. Data: In vitro studies that compared the antibacterial effects of resin-based restorative dental materials with and without antibacterial additives were screened. Risk bias was assessed, and the following data were extracted: antibacterial additive, parental dental material, curing mode, bacterial growth outcome assessment, samples used as a substrate for bacterial growth, inoculum complexity, and culture time as an indicator of biofilm maturity. Source: Arksey and O'Malley's five stages framework using Medline (OVID), EMBASE, and Scopus (Elsevier) databases guided this review. Study selection: From 6503 studies initially identified, 348 studies were considered eligible for full-text screening, and 153 were included for data extraction. Almost all studies have a high sampling bias related to both sample size and blindness. Quaternary ammonium monomers were the most investigated additive (45 %), and the most prevailing parental material was resin composite (49 %). There was extensive methodological heterogeneity among the studies for outcome assessment with the majority using resin composite disks (78 %), mono-species Streptococcus mutans as the inoculum (54 %), and a relatively short period of biofilm growth (≤24 h). Conclusion: The findings herein present the urgent need for improved biological efficacy studies in this important and exciting field. There is a need for efforts to improve study designs to mimic the oral environment in vivo and to develop standardized methods to help understand and optimize these materials. Clinical significance: Most studies that incorporate antibacterial additives into resin-based materials claim promising results by bacterial reduction. However, these results should be interpreted with caution due to significant variation in the methods applied for quantifying bacterial growth, the frequent lack of complexity in the biofilms, and the often-short duration of biofilm growth.